PID controller design for asymmetrical temperature control - Yükselten, Mehmet Sait. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
In today’s industrial environments, there is an increasing number of modelling and controlling researches of the processes which are used in many types of applications. However, there are only some limited researches on asymmetrical processes. Temperature control system is a common example of those processes. Some examples to that are industrial oven and furnace, air conditioned mediums, medicine and dye factories, food industry, heating and cooling systems and so on. The asymmetrical processes are the systems whose dynamics may change depending on the direction. In those systems, since the powerful heaters, the heating process realizes rapidly but that the cooling process slowly. That’s why, the classical PID control method may not be enough to get the desired results. On this project, we developed a new model by firstly reducing the overshoot and minimizing the settling time with Full power and PWM modes. Then, we made some improvements on the standard PID method to get a system output like symmetrical behaviour. In order to test the applied model, we developed a full control system with a microcontroller based embedded board and a user interface on PC to be controlled by the user. The system mainly consists of a heating rezistance, thermocouple, microcontroller based board and a PC to visualize the system. In this project, firstly the general characteristics of the asymmetrical processes are discussed and then a new control model is presented with some complicated methods. After talking about the software and the hardware models, the results are discussed.
Keywords: PID controllers.